Space–time distribution of the ALS incident cases by onset type in the Health District of Ferrara, Italy. (14th October 2014) - Govoni, V.; Della Coletta, E.; Cesnik, E.; Casetta, I.; Tugnoli, V.; Granieri, E.
Abstract : Objectives: An ecological study in the resident population of the Health District (HD) of Ferrara, Italy, has been carried out to establish the distribution in space and time of the amyotrophic lateral sclerosis (ALS) incident cases according to the disease onset type and gender in the period 1964–2009. Material and methods: The hypothesis of a uniform distribution was assumed. Results: The incident cases of spinal onset ALS and bulbar onset ALS were evenly distributed in space and time in both men and women. The spinal onset ALS incident cases distribution according to gender was significantly different from the expected in the extra‐urban population (20 observed cases in men 95% Poisson confidence interval 12.22–30.89, expected cases in men 12.19; six observed cases in women 95% Poisson confidence interval 2.20–13.06, expected cases in women 13.81), whereas no difference was found in the urban population. The spinal onset ALS incidence was higher in men than in women in the extra‐urban population (difference between the rates = 1.53, 95% CI associated with the difference 0.52–2.54), whereas no difference between sexes was found in the urban population. Conclusions: The uneven distribution according to gender of the spinal onset ALS incident cases only in the extra‐urban population suggests the involvement of a gender related environmental risk factor associated with the extra‐urban environment. Despite some limits of the spatial analysis in the study of rare diseases, the results appear consistent with the literature data.